The Effectiveness of Academic Supervision of PAI Subjects at SDIT Nurul Fikri Palangka Raya - Marni, Marni; Kurniawati, Triyani (Transformatif, 2023)
This study analyzes the effectiveness of the implementation of principal supervision of PAI learning process standards at SD IT Nurul Fikri Palangka Raya. This study aims to determine the process of preparing the supervision program, the techniques applied, and the implementation of supervision carried out by the principal of Nurul Fikri Palangka Raya. The method used in this research is a descriptive qualitative method and data collection using interview, observation, and documentation techniques. The research subject is the Principal of SDIT Nurul Fikri Palangka Raya. This study examines the implementation of the principal's supervision of the Islamic Religious Education (PAI) learning process standards at SDIT Nurul Fikri Palangka Raya. Through an interview with the principal, Mrs. Lina Indah Purwati, M.Pd, on October 2023, this research highlights the effectiveness of supervision planning, implementation, and evaluation. The results showed that the principal had planned the supervision program well, focused on teachers' difficulties in teaching, and carried out supervision regularly. Evaluation of the results of supervision is done carefully, and appropriate follow-up is given to PAI teachers. This is the principal's effort to improve the quality of PAI learning and realize the school's vision as an educational institution that implements national standards. Thus, the principal's supervision has helped in achieving these goals